Jenis Pola Asuh Orangtua yang Tepat untuk Anak dengan Attention Deficit Hyperactivity Disorder (ADHD): Tinjauan Sistematis Literatur - Jingga Tsabitah; Nada Izdihar Firdausa; Icha Diana Putri; Hanifa Laura Dalimunthe (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
This study aims to identify the types of parenting patterns most often used in assisting children with Attention Deficit Hyperactivity Disorder (ADHD) and assess the effectiveness of each parenting pattern. This study used the Systematic Literature Review (SLR) method on 16 scientific articles published between 2015-2025 and obtained from various databases such as Google Scholar, PubMed, and ScienceDirect. The results showed that authoritative (democratic) parenting is the most widely used and most effective approach for children with ADHD. It is characterized by a combination of emotional support and consistent supervision, which has been shown to reduce ADHD symptoms and improve children's social and executive functioning. In contrast, authoritarian and permissive parenting tends to worsen the condition of ADHD children. Factors such as parental education level, parenting experience, and family structure were also found to influence the type of parenting practiced. These findings emphasize the importance of choosing the right parenting style to support the optimal development of children with ADHD.